Overview of Early Initiation Breastfeeding and Increasing Temperature in Newborn - Mona, Silvia; Prasida Yunita (HM Publisher, 2022)
This study aims to determine the description of initiation early breastfeeding and increased body temperature of newborns. This research is an observational study with a cross-sectional design. The study was conducted at the Suratmi midwife maternity clinic in Batam City. The study population was mothers who had just given birth from February to March 2022. The inclusion criteria in this study were mothers who had just given birth at the clinic, aged 20-40 years, and were willing to participate in the study. Sampling was done by the purposive sampling technique. The results showed that the early initiation of breastfeeding (EIB) was achieved by 36 respondents with an increase in temperature of 0.20C as many as 18 respondents (45%) and an increase in temperature of 0.30C by 4 respondents. In conclusion, most of the new mothers have achieved early initiation of breastfeeding and there is an increase in the baby's body temperature of 0.1-0.2OC.